Exporting American Dreams : Thurgood Marshall's African Journey - Dudziak, Mary L. (Book collections on Project MUSE., 2011)
Mary Dudziak's Exporting American Dreams tells the little-known story of Thurgood Marshall's work with Kenyan leaders as they fought with the British for independence in the early 1960s. Not long after he led the legal team in Brown v. Board of Education, Marshall aided Kenya's constitutional negotiations, as adversaries battled over rights and land--not with weapons, but with legal arguments. Set in the context of Marshall's civil rights work in the United States, this transnational history sheds light on legal reform and social change in the midst of violent upheavals in Africa and America.